You are judged by the company you keep: Reputation leverage in vertically related markets - Jay Pil Choi; Martin Peitz (University of Mannheim, Department of Economics, 2016)
This paper analyzes a mechanism through which a supplier of unknown quality can overcome its asymmetric information problem by selling via a reputable downstream …rm. The supplier’s adverse-selection problem can be solved if the downstream …rm has established a reputation for delivering high quality vis-à-vis the supplier. The supplier may enter the market by initially renting the downstream …rm’s reputation. The downstream …rm may optimally source its input externally, even though sourcing internally would be better in terms of productive e¢ ciency. Since an entrant in the downstream market may lack reputation, it may su¤er from a reputational barrier to entry arising from higher input costs.
urn:nbn:de:bsz:180-madoc-405603
Keywords: D4; L12; L4; L43; L51; L52; 330; Adverse Selection; Certi fication Intermediaries; Incumbency Advantage; Experience Goods; Outsourcing; Branding; Barriers to Entry; Lieferantenmanagement; Marketingkooperation; Reputation; Adverse Selektion; Erfahrungsgüter; Outsourcing; Signalling; Theorie